Fracture Resistance Of Cad/Cam Occlusal Veneers Constructed From Glass And Hybrid Ceramics With Two Preparation Designs “An In -Vitro Study” (Journal of Pharmaceutical Negative Results, 2023)
Statement of Problem. The information regarding the influence of the type of ceramic material and the preparation design on the fracture resistance of occlusal veneers for treatment of patients with severe wear is still insufficientPurpose. Purpose of the study was to analyze the fracture resistance and the failure mode of lithium disilicate and hybrid ceramic materials with various preparation designs to be used as bonded occlusal veneers.Material and Methods.Two mandibular first molars of a typodont were used for the master preparations; one for the conventional planar design and the second for the modified design, the preparations were duplicated into twenty epoxy resin dies over which the occlusal veneers were adhesively cemented. Each group of epoxy resin dies was subdivided randomly into two equal subgroups according to the ceramic material to be tested; lithium disilicate "Rosetta " and the hybrid ceramic "VITA ENAMIC". Then the fracture resistance and failure mode of occlusal veneers were evaluated.Results: The results showed that the type of ceramic material and the preparation design had no statistically significant effect on the fracture resistance of occlusal veneers.Conclusions: All the tested CAD/CAM materials showed fracture loads above the recommended minimum fracture strength for posterior restorations with different preparation designs.